Estruturação de comunidades de aves em uma paisagem urbanizada da floresta atlântica nordestina - Enedino, Thayz Rodrigues (2015)
Currently the Brazilian Atlantic Forest is considered one of the world's biodiversity repositories, however fragmentation, habitat loss, strong urbanization and other human disturbance have degraded its rich biological heritage and altered ecological processes that ensure their persistence. Paraiba remain some fragments of forests that are protected by law, but little is known about the level of change in the structure of the remaining biological communities, especially the birds. In addition to identifying the species found in protected areas of the state, the objective was also to test the hypothesis that urbanization reduces the number of species of birds, leading to taxonomic convergence and functional impoverishment of communities, especially in small forest remnants and isolated. The study was conducted in the Paraíba River Estuary region in the northern portion of the Atlantic Forest, inserted in Pernambuco Endemism Center. The sampling was performed by birds MacKinnon lists nine protected areas. We recorded 126 species of birds belonging to 41 families, Thraupidae and Tyrannidae being the most representative families. Nineteen species occurred in the nine protected areas, Pitangus sulphuratus (Great Kiskadee) lists the most common (52.9% of the lists). Two exotic species were recorded (Estrilda astrild and Passer domesticus). About 90% of the observed variation in species richness were explained only by the fragment size, indicating that habitat loss due to urbanization is a major cause of biological erosion in the region. The Taxonomic similarity between areas ranged from 36.5% to 71.4% (mean 52.6%), but did not correlate strongly with the geographical distance or the difference in size of the protected area. This shows that protected areas near or with similar sizes have different avifaunas. Functionally, smaller fragments of communities had proportionally more species susceptible to disturbance, foraging in the air and less foraging in undergrowth. The proportion of endemic or threatened species did not vary depending on the area. Taken together, our results indicate that the loss of habitat due to urbanization results in the loss of species and functional depletion of forest fragments, but does not necessarily lead to convergence Taxonomic the remaining communities. It is recommended that the management of the studied areas is done in an integrated manner to ensure the conservation of birds on a regional scale.